2013
DOI: 10.1002/stem.1487
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D3 critically regulates the balance between self-renewal and differentiation in skeletal muscle stem cells

Abstract: Satellite cells are mitotically quiescent myogenic stem cells resident beneath the basal lamina surrounding adult muscle myofibers. In response to injury, multiple extrinsic signals drive the entry of satellite cells into the cell cycle and then to proliferation, differentiation, and self-renewal of their downstream progeny. Because satellite cells must endure for a lifetime, their cell cycle activity must be carefully controlled to coordinate proliferative expansion and self-renewal with the onset of the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 80 publications
2
33
0
Order By: Relevance
“…**, p Ͻ 0.01. those found in vivo and confirm that lipin1 is essential for effective differentiation during the early stages of myogenesis. Our data are in agreement with previous studies that ERK2 and cyclin D3 are critical for myoblast terminal differentiation (30,31).…”
Section: Lipin1 Is Required For Myoblast Differentiation and Lipin1-dsupporting
confidence: 94%
See 2 more Smart Citations
“…**, p Ͻ 0.01. those found in vivo and confirm that lipin1 is essential for effective differentiation during the early stages of myogenesis. Our data are in agreement with previous studies that ERK2 and cyclin D3 are critical for myoblast terminal differentiation (30,31).…”
Section: Lipin1 Is Required For Myoblast Differentiation and Lipin1-dsupporting
confidence: 94%
“…This is consistent with previous observations that cyclin D3 knock-out mice exhibited decreased myofiber size at 21 days of regeneration and that cyclin D3 deficiency was associated with reduced proliferative capacity and impaired G 1 /S progression (31,37,38). In contrast, cyclin D3 overexpression promotes myogenic differentiation as demonstrated by increased MyoD and MyoG expression (37).…”
Section: Volume 290 • Number 39 • September 25 2015supporting
confidence: 93%
See 1 more Smart Citation
“…This clearly shows that the beginning of the differentiation program induced by 1,25D in C2C12 cells requires the expression of the VDR and activation of p38. However, in cyclin D3-deficient C2.7 myoblasts, changes in myogenin expression were not found (De Luca et al 2013). This may be explained by differences in experimental design (like the use of differentiation medium) or other pathways which are not regulated by 1,25D being involved in myogenin expression.…”
Section: Discussionmentioning
confidence: 91%
“…8,11,38,39 However, the study of CCND3 regulation in B cells is yet to be fully understood. In this study, we first found that elevated CCND3 was associated with SLE based on gene profiling analysis.…”
Section: Discussionmentioning
confidence: 99%